Genetic diversity analysis of mitochondrial DNA control region in artificially propagated Chinese sucker Myxocyprinus asiaticus. (August 2015) - Wan, Yuan; Zhou, Chun-hua; Ouyang, Shan; Huang, Xiao-chen; Zhan, Yang; Zhou, Ping; Rong, Jun; Wu, Xiao-ping
Abstract The genetic diversity of the three major artificially propagated populations of Chinese sucker, an endangered freshwater fish species, was investigated using the sequences of mitochondrial DNA (mtDNA) control regions. Among the 89 individuals tested, 66 variable sites (7.26%) and 10 haplotypes were detected (Haplotype diversity Hd = 0.805, Nucleotide diversity π = 0.0287). In general, genetic diversity was lower in artificially propagated populations than in wild populations. This reduction in genetic diversity may be due to population bottlenecks, genetic drift and human selection. A stepping-stone pattern of gene flow was detected in the populations studied, showing much higher gene flow between neighbouring populations. To increase the genetic diversity, wild lineages should be introduced, and more lineages should be shared among artificially propagated populations.